IMPLEMENTATION STRATEGIES FOR INFANT AND CHILD TRAINING IN NURSERIES: ALIGNING WITH THE ASPIRATIONS OF MODERN PARENTS - NURUL NADIA MOHD ZAYID; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This library study examines the implementation strategy of the teaching and learning approach (PdP) for infants (0–12 months) and toddlers (1–3 years) at TASKA that is in line with the aspirations of today's parents. The latest literature from 2020 to 2025 is used as the main reference. The main findings emphasize five important aspects: development-based play, safety and hygiene (K3), home–TASKA communication, development monitoring, and the inculcation of early values and manners. This study suggests the implementation of structured play routines, the use of robust K3 protocols, transparent communication mechanisms, brief developmental assessments, and emphasizing Islamic values in children's daily lives. In conclusion, a comprehensive PdP can meet the expectations of today's parents for their children's early education (Yoke-Yean et al., 2021; Rahmatullah et al., 2021).